Design and Implementation of a Web Service-Based Middleware Application for PDDIKTI Reporting at XYZ University - Harkat Christian Zamasi (Engineering, MAthematics and Computer Science Journal (EMACS), 2026)
Reporting of academic data to the Higher Education Database (PDDIKTI) is an obligation for every university in Indonesia that must be done accurately and timely in accordance with government regulations. However, in practice, the reporting process is still largely manual via the Neo Feeder application. This causes problems in efficiency, data consistency and possible delays in reporting, particularly in universities with large volumes of academic data. Although PDDIKTI has provided web services facilities, their utilization as part of the Extract, Transform, and Load (ETL) middleware architecture has not been optimally implemented. However, the integration of internal academic information system with PDDIKTI still has problems related to the difference of data structure, business rules and technology platform used and the absence of a generally replicable middleware model. This study aims to design and implement the ETL middleware architecture model based on web services Neo Feeder as a solution for the automation of PDDIKTI data reporting. The research method used is applied research (applied research) with an approach to information systems engineering, which consists of the stages of needs analysis, design of system architecture, implementation and evaluation of prototypes in a case study of XYZ University. The results of this study indicate that the proposed ETL middleware architecture model can integrate internal academic information systems with PDDIKTI in an automatic, structured and controlled manner, thus increasing the efficiency and timeliness of academic data reporting. The resulting architecture model and prototype are generic and can be replicated by other universities as a reference for implementing integrated PDDIKTI data reporting in line with the One Data Higher Education policy.